ANTI-DIABETIC POTENTIAL OF Spatoglossum asperum (BROWN SEAWEED); INSILICO MODEL - SEKAR, ANDREWS; CHELLADURAI, GURUSAMY; VAITHILINGAM, SUBRAMANIYAN; PANDIAN, ARJUN; SIVALINGAM, AZHAGU MADHAVAN; SIVAMANI, GANESAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
This study used GC-MS analysis and computational biology to examine the diabetic effect of bioactive substances obtained from brown seaweed. Using AutoDock/Vina in Pymol 4.2, the molecular docking of Spatoglossum asperum on the human PPAR- protein was determined and compared to that of the well-known PPAR- agonist Gilbenclamide. The analysis the active components of seaweed extracts is the main focus of the current investigation. 12 substances were discovered using GC-MS analysis and evaluated using AutoDock/Vina against PPAR. Docking tests showed that the existing phytochemical 9-Octadecenoic Acid (Z)-, Octadecyl Ester, obtained from seaweed, has the highest fitness score of -398.9 kcal/mol and may therefore be a potent anti-diabetic drug. This study could result in the creation of brand-new marine nutraceuticals that use brown seaweed to treat a number of diseases.